Dry-cured meat products - Toldrá, Fidel (Food & Nutrition Press, 2002)
Toldra' presents the latest developments in dry-cured meat products from raw materials and manufacture to the final products. The text also includes current scientific and technological information on the safety, quality, and nutritional properties of such foods. Written as a text for advanced undergraduate and graduate students, and as a reference for basic/applied scientists in this field, and food technologists in quality control and research and development in the meat industry.